PENGARUH SERTIFIKASI GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU ASN DI SMP NEGERI MADANG SUKU I - Mareta Maharani; Meilia Rosani; Mulyadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of teacher certification and work motivation on the performance of ASN teachers at SMP Negeri Madang Suku I. Teacher certification is a government effort to improve the competence and professionalism of educators, while work motivation is an internal factor that encourages teachers to carry out their duties optimally. Good teacher performance is expected to improve the quality of learning and student learning outcomes. This study uses a quantitative approach. Data were collected through questionnaires distributed to ASN teachers at SMP Negeri Madang Suku I. Data analysis was carried out using multiple linear regression techniques to determine the effect of independent variables on dependent variables. The results showed that teacher certification had a positive and significant influence on teacher performance. Likewise, work motivation had a positive and significant effect on the performance of ASN teachers. In addition, simultaneously, teacher certification and work motivation contributed significantly to improving teacher performance. This finding confirms that the certification policy needs to be accompanied by an increase in work motivation so that teacher performance is increasingly optimal.